Clinical Aspects of Miscarriage. Issue 1 (January 2018) - Walter, Marie A.; Alvarado, Mary S.
Abstract : Abstract: It is estimated that 750, 000 to 1, 000, 000 miscarriages occur every year in the United States. Women experiencing a miscarriage enter the healthcare system in a variety of ways. A family may be seen for a miscarriage in the prenatal clinic, the emergency department, same-day surgical department, or perhaps the labor and birth unit. Nurses must be prepared to guide and support these families. Understanding the clinical aspects of miscarriage as well as the emotional care of families experiencing early pregnancy loss is important to nurses in all areas of the medical center. Clinical aspects of miscarriage are reviewed along with the needed emotional care for families experiencing the most common cause of early pregnancy loss. Abstract : Understanding the clinical aspects of miscarriage, as well as the emotional care of families experiencing early pregnancy loss, is important to nurses in all areas of the hospital. A clinical review and recommendations for care are offered for nurses caring for women who have a miscarriage.